Analysis the Age of Pregnant Woman and Stages of Hypertension as Risk Factors of Preeclampsia Eclampsia on Pregnant Women in Dr. Murjani General Hospital Sampit at June Periode 2018 - Herli Gustiani (Fakultas Kedokteran Universitas Lambung Mangkurat, 2018)
Abstract: Preeclampsia is a syndrome characterized by an increase in blood pressure and proteinuria that appears in the second trimester of pregnancy which is always recovered in the postnatal period. Preeclampsia can be influenced by many factors, but the analysis of risk factors for preeclampsia in Dr. Murjani Hospital has never been done, especially in relation to the pregnant women age, history of pregnancy, abortion, and stages of hypertension. Thus, this research needs to be done. This research was analytical study with cross sectional approach, which aims to explain the relationship between the age of pregnant women and the stages of hypertension with preeclampsia. Research subjects were patients who came to Dr. Murjani Hospital on 28 May-9 June 2018. Data were collected from the Medical Record section and analyzed by t-test to compare the average of two groups (normal and preeclampsia). Chi Square test with 95% confidence interval was used to find out the relationship between two variables. The results showed that there was no relationship between the age of pregnant mother with preeclampsia incident in Dr. Murjani Hospital, but the stages of hypertension is related with preeclampsia incident in Dr. Murjani Hospital. Keywords: preeclampsia, stage of hypertension, the age of pregnant women